Potential of Herbal Essential Oils as Denture Cleansers Against Biofilm Formation on Dental Acrylic Resin: In Vitro and In Silico Approaches - Nurdan Polat Sağsöz; Leyla Güven; Bahri Gür; Mustafa Cengiz; Canan Vejselova Sezer; Figen Orhan; Özlem Barış (Journal of Chemistry)
Commercial denture cleansers for biofilm removal in dental acrylic resin reduce gloss, alter surface hardness and roughness, and cause discoloration. The present study aims to investigate the effects of different essential oils, Rosmarinus officinalis (ROEO), Cinnamomum zeylanicum (CZEO), and Pelargonium graveolens (PGEO), on the preformed biofilm of Candida albicans in dental resin samples in vitro and in silico. The concentration of essential oils was evaluated using gas chromatography–mass spectrometry (GC–MS). Sterile polymethyl methacrylate samples were treated with essential oils and a chemical denture cleaner tablet (DCT) to remove adhering C. albicans. The essential oil activity was analyzed via absorbance at 600 nm, with cytotoxicity assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. In silico studies elucidated the molecular mechanism of the anticandidal effect. The anticandidal effect of CZEO was highest at a low concentration, while that of CZEO, PGEO, and ROEO at a high concentration was similar but higher than that of DCT. In NIH/3T3 cells, ROEO, CZEO, and PGEO showed cytotoxic effects at concentrations of 5, 1.25, and 2.5 μg/mL and higher, respectively, after 24 h. According to the in silico studies, secreted asparagine proteinase (SAP-2) inhibition was higher at a 2% concentration of CZEO. For PGEO and ROEO, higher SAP-2 inhibition was observed at a concentration of 5%. At a concentration of 2% and 5%, PGEO, CZEO, and ROEO effectively suppressed the activity of SAP-2 protein and inhibited the development of C. albicans biofilms on acrylic resin. The in silico study showed that the most effective inhibition can be attributed to the presence of carvacrol in CZEO.